Remnant cholesterol as a risk factor for cardiovascular, cancer or other causes mortality: A competing risks analysis - Bonfiglio, Caterina; Leone, Carla M.; Silveira, Liciana V. A. [UNESP]; Guerra, Rocco; Misciagna, Giovanni; Caruso, Maria G.; Bruno, Irene; Buongiorno, Claudia; Campanella, Angelo; Guerra, Vito M. B.; Notarnicola, Maria; Deflorio, Valentina; et al. (Elsevier B.V., 2020)
Background and aims: Cardiovascular diseases (CVDis) are leading causes of morbidity and mortality. Even after the introduction of pharmacological therapy to lower Cholesterol, there is still a residual risk that may be ascribed to remnant cholesterol (RC). We aimed, by analyzing two prospective cohort studies, to estimate the effect of RC on risk and hazard of cardiovascular deaths ( CVDs), while accounting for competing risks such as cancer ( CDs) and other-causes deaths (OCDs). Methods and results: Cohorts were enrolled in 1992 and 2005. Personal data history was recorded. A fasting venous blood sample was obtained, and RC was calculated at baseline. Cause of Death was coded by using ICD-10th version. Follow-up ended on December 31, 2017. Flexible parametric competing-risks models were applied, with age at death as time-axis. In total, 5729 subjects were enrolled. There were 861 (15.1%) deaths: 234 CVDs (27.2%), 245 CDs (28.5%), 271 OCDs (31.5%) and 111 unknown causes of death (12.8%). RC exposure was a strong risk factor only for CVDs (Risk 2.54, 95% Confidence Interval 1.21; 5.34; Trend 1.26 (1.00; 1.58) for >= 1.29 mmol/L). Conclusions: RC is a strong independent risk factor for cardiovascular mortality. Competing risk analysis is demonstrably a useful tool to disentangle associations among different competing events with a common risk factor. (C) 2020 The Italian Diabetes Society, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition and the Department of Clinical Medicine and Surgery, Federico II University. Published by Elsevier B.V. All rights reserved.
Keywords: Cause-specific mortality; Competing-risks; Remnant cholesterol; Survival analysis